ANALISA PARAMETER GENETIK SIFAT KAYU KOMBINASI UJI PROVENANS DAN UJI KETURUNAN ACACIA MANGIUM DI KALIMANTAN SELATAN - Mudji Susanto; Muhammad Na'iem; Eko Bhakti Hardiyanto; T.A. Prayitno (Jurnal Pemuliaan Tanaman Hutan, 2012)
Combination of provenance progeny trial of Acacia mangium from Claudie River-Queensland- Australia was established in Pelaihari, South Kalimantan. The objective of this research is to find variation on diameter, wood specific gravity and fiber lenght between provenance seedlot and family within provenance seedlot in provenance progeny trial of A. mangium on 22 months old.The results showed that the mean of wood specific gravity and was 0.40 and mean of fiber length was 0.89 mm. Variation of diameter, wood specific gravity, and fiber length were significant difference among provenance seedlot or between family within provenance seedlot in the trial. Individual heritability of diameter, wood specific gravity, and fiber length were medium (hi 2=0.49 for diameter; hi 2=0.33 for specific gravity and hi 2=0.39 for fiber length). The results of investigation from this trial indicate that diameter, wood specific gravity, and fiber length are necessary to be used for tree selection to improve growth wood quality in the combination of provenance progeny trial of A. mangium.